Poverty and Foreign Investment and their impact on HDI in West Java Province (2010-2022 period) - Perkasa Alam, Bambang; Yolanda, Yolanda; Arifin, Zainal (Finance : International Journal of Management Finance, 2024)
This research aims to analyze the relationship between poverty and foreign investment (PMA) and its impact on the Human Development Index (HDI) in West Java Province during the 2010-2022 period. The research method uses a descriptive-analytical approach by collecting economic, social and investment data from official sources. The results of the analysis show that there is a correlation between the level of poverty and foreign investment in West Java. Economic growth achieved through FDI has had an impact on reducing poverty levels, but the pattern of distribution of wealth and economic benefits is still a challenge. Apart from that, this research also evaluates the positive and negative impacts of FDI on the Human Development Index in the region. The findings of this research can contribute to the understanding of the complexity of the relationship between poverty, foreign investment and human development at the regional level. Policy implications are suggested to improve the effectiveness of PM economic benefit distribution).